Color two-dimensional code anti-counterfeiting method based on support vector machine - WU HUAMING; HUANG LIZHEN; XIAO WENBO; FU YANJUN; CAO JINMING; CHEN HEPU; XIAO YONGSHENG; ZHANG YECHAO (2021)
The invention discloses a color two-dimensional code anti-counterfeiting method based on a support vector machine, and the method comprises the steps: firstly generating a color two-dimensional code containing a watermark, then collecting a color two-dimensional code image through employing an APP application program, carrying out the preprocessing, extracting texture and color combination features through employing a gray-gradient co-occurrence matrix method and a color space conversion method, finally, training the image data by using a support vector machine (SVM) algorithm to establish a model, and distinguishing the image data of the test set. The designed two-dimensional code anti-counterfeiting system can better distinguish the printed image and the copied image of the color two-dimensional code, and solves the anti-counterfeiting problem of the current two-dimensional code. 本发明公开了一种基于支持向量机的彩色二维码防伪方法，该方法首先生成含水印的彩色二维码，其次利用APP应用程序采集彩色二维码图像并进行预处理，然后使用灰度-梯度共生矩阵法及颜色空间转换法，提取纹理和颜色组合特征，最后使用支持向量机(SVM)算法训练图像数据以建